Aplicação do termocondicionamento e da relação eletrolítica na criação de frangos de corte: Maria clara da Silva Minello. - - Minello, Maria Clara da Silva [UNESP] (2015)
In tropical climates, heat is one of the most important limiting factor for the production of broiler chickens, being responsible for high mortality, especially in the final period of the raising. This study evaluated the effects of thermoconditioning (TC) and feed considering electrolyte balance (EE) as a way to reduce this effect. 300 male chicks Cobb 500 were randomly assigned for six repetitions of four treatments in a 2 x 2 factorial scheme: (T1) feed without EE without TC, (2) feed without EE with TC, (3) feed with EE without TC and (4) feed with EE with TC. The thermoconditioning was held on the 5th day totaling 24 hours at 36 oC. After this period, the birds were transferred to boxes with wood shavings bed, where they remained until the end of the experiment. Acute thermal stress was applied at the 36º day, for 6 hours, in all treatments. Feed and water were provided ad libitum during the full experiment period, even during the thermal stress. The performance parameters investigated were weight gain (WG), feed conversion (FC), body weight (BW), guts weight (GW) and mortality (%M). The results showed that both TC and EE were effective in reducing the mortality without altering the performance of the birds and suggested a potentiation effect when they were used simultaneously. At the treatment in which none of these strategies was adopted, the mortality rate was 83% higher, compared to the treatment in which both were applied. Therefore, both techniques were considered suitable for reducing the damage caused by heat in the raising of broiler chicken